Acute Myeloid Leukemia Presenting as Acute Appendicitis. (11th June 2013) - Rauenzahn, Sherri; Armstrong, Caroline; Curley, Brendan; Sofka, Sarah; Craig, Michael
Abstract : Appendicitis in leukemic patients is uncommon but associated with increased mortality. Additionally, leukemic cell infiltration of the appendix is extremely rare. While appendectomy is the treatment of choice for these patients, diagnosis and management of leukemia have a greater impact on remission and survival. A 59-year-old Caucasian female was admitted to the surgical service with acute right lower quadrant pain, nausea, and anorexia. She was noted to have leukocytosis, anemia, and thrombocytopenia. Abdominal imaging demonstrated appendicitis with retroperitoneal and mesenteric lymphadenopathy for which she underwent laparoscopic appendectomy. Peripheral smear, bone marrow biopsy, and surgical pathology of the appendix demonstrated acute myeloid leukemia (AML) with nonsuppurative appendicitis. In the setting of AML, prior cases described the development of appendicitis with active chemotherapy. Of these cases, less than ten patients had leukemic infiltration of the appendix, leading to leukostasis and nonsuppurative appendicitis. Acute appendicitis with leukemic infiltration as the initial manifestation of AML has only been described in two other cases in the literature with an average associated morbidity of 32.6 days. The prompt management in this case of appendicitis and AML resulted in an overall survival of 185 days.